Faciès, biostratigraphie et paléogéographie du Jurassique portugais - Mouterde, R. (2008)
The facies distribution along the Jurassic stages in an already well established stratigraphic frame is defined for the three portuguese basins: North of Tagus, Santiago de Cacém and Algarve. The deposits are organized in two sedimentary cycles. The first one from the Liassic to Calovian shows, in the Tagus Basin, a transgression from NW which did not surpass the Meseta present limits. The iniatilly brackish deposits only changed to marine by the end of Lotharingian. The sedimentation, mainly marly during the Liassic became more calcareous since the Aalenian. During the Dogger the basin differentiated into platform deposits towards East and South and open sea zone towards West. This zone underwent a progressive reduction and, during the Callovian, two small basins were individualized: Cabo Mondego basin in the North and Serra de El-Rei-Montejunto in the South. It is from the latter that the second sedimentary cycle (Middle Oxfordian-Portlandian) developed with open sea deposits along the Sintra–Torres Vedras axis surrounded by platform and litoral brackish formations. During the first sedimentary cycle only litoral platform deposits are known in Santiago de Cacém and Algarve basins. During the second sedimentary cycle temporary sea open deposits are known in Santiago de Cacém and Central Algarve.